The Humorous Aspect of Religious Messages Popular in Generation Z on Social Media: A Study of Religious Students in Samarinda - Afita Nur Hayati; Ramadiva Muhammad Akhyar (Jogjakarta Communication Conference (JCC), 2026)
As digital natives, Generation Z spends over six hours daily on social media. One type of content they access is Islamic content. However, the themes most commonly associated with this content remain a topic of ongoing debate. This study aims to examine Generation Z's preferences for Islamic content on social media within tertiary-level religious studies programs. A mixed-methods approach was employed, beginning with a quantitative survey followed by qualitative analysis, with data collected via a Google Form completed by 86 undergraduate students at a state Islamic religious university in Samarinda. Data were analyzed using descriptive statistics and thematic analysis. The findings indicate that (1) the most popular social media platforms are Instagram and WhatsApp, (2) Generation Z tends to be uniform in consuming Islamic messages, with 83.7% preferring Islamic content that includes humor, followed by inspirational themes, for various reasons. These results suggest that adding humorous elements to Islamic content can help make these messages more accessible, understandable, and relevant to Generation Z. This study recommends that Muslim influencers incorporate humor into their Islamic content, provided it does not overshadow the core message. This approach aims to capture Generation Z’s attention and foster full engagement with Islamic messages.